Promanodes alleni sp. nov., the second species of the Tertiary genus Promanodes Kolibáč, Schmied, Wappler et Kubisz, 2010, with improved diagnosis of the genus and remarks on its phylogeny (Coleoptera: Trogossitidae) - Kolibáč, Jiří (Zootaxa, 2011)
A new species of the genus Promanodes Kolibáč, Schmied, Wappler et Kubisz, 2010 (Trogossitidae: Lophocaterinae: Lophocaterini), P. alleni sp. nov., is described from Baltic amber. Perfectly visible antennae and tarsi of the fossil extend morphological information about the genus and new character states, some of them unique among Peltinae and Lophocaterinae, confirm its independent status. A differential diagnosis of Promanodes is improved. A character analysis confirms a relation of Promanodes and the extant genus Promanus Sharp, 1877.